Fanny Hill, by John Cleland, and as Mulheres de Mantilha, by Joaquim Manuel de Macedo: A Reflexion About the False Morality Defended in Novels - Fardin, Gabriela [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2018)
This work is a proposal of reading and interpretation of the books Fanny Hill or Memories of a Woman of Pleasure (1748-9), written by John Cleland (1710-89); and As Mulheres de Mantilla: romance historico (1870), written by Joaquim Manuel de Macedo (1820-82). We will focus here on the passages of the novels that demonstrate the idea of a false morality advocated by the authors, it seems to us, only to protect their own faces of the judgments of their reading community.
Keywords: As Mulheres de Mantilha; Fanny Hill; Joaquim Manuel de Macedo; John Cleland